2015 IEEE 18th International Conference on Computational Science and Engineering 2015
DOI: 10.1109/cse.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

Combining Keystroke Dynamics and Face Recognition for User Verification

Abstract: Abstract²The massive explosion and ubiquity of computing devices and the outreach of the web have been the most defining events of the century so far. As more and more people gain access to the internet, traditional know-something and have-something authentication methods such as PINs and passwords are proving to be insufficient for prohibiting unauthorized access to increasingly personal data on the web. Therefore, the need of the hour is a user-verification system that is not only more reliable and secure, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, Fenu, Marras and Boratto building a template containing features of the following five modalities, face images, voice data, touch data, mouse data, and keystroke dynamics [82]. The student's face will be captured and stored in addition to the student's dynamic keystrokes [14,83,84]. Alternatively, Shen, et.al.…”
Section: Multi-factorsmentioning
confidence: 99%
“…For example, Fenu, Marras and Boratto building a template containing features of the following five modalities, face images, voice data, touch data, mouse data, and keystroke dynamics [82]. The student's face will be captured and stored in addition to the student's dynamic keystrokes [14,83,84]. Alternatively, Shen, et.al.…”
Section: Multi-factorsmentioning
confidence: 99%
“…In this regard, biometric features unique to individuals, ranging from physiological characteristics (e.g., fingerprints and iris, hand, and face patterns) to behavioral characteristics (e.g., KD, www.ijacsa.thesai.org mouse movements, gait, and handwriting), have served to identify users [3]. Many such biometric approaches tend either to be expensive or to place heavy demands on computer hardware, making them inappropriate for most users [35].…”
Section: B Multifactor Authentication (Mfa)mentioning
confidence: 99%
“…Jadhav Kulkami, Shelar, Shinde, and Dharwadkar [3] proposed an ML-based authentication model that uses the static approach of keystroke dynamics to recognize and authenticate users accessing the system based on their unique keystroke profiles with respect to the flight, dwell, press, press-to-press, and release-to-release time and achieved an FAR and an FRR of 1% and 4%, respectively. Gupta, Khanna, Jagetia, Sharma, Alekh, and Chouldhary [35] proposed a high-efficiency authentication system combining two methods to make keystroke biometrics less susceptible to forgery and more usable and reported that the system efficiently implemented secure authentication with the advantage of ease of implementation since all that is required is the installation of software on any workstation. Yang et al [55] focused on the text entered by the user and proposed contents and keystroke dual attention networks (ML) with pre-trained models for continuous authentication to address user-inputted -text‖ during keystrokes as an important asset beyond traditional KD characteristics, and their model achieved state-of-the-art performance on two datasets.…”
Section: Behavioral Authentication Using MLmentioning
confidence: 99%